Using Learning Analytics to Improve Students’ Reading Skills: A Case Study in an American International School with English as an Additional Language (EAL) Students (GIST – Education and Learning Research Journal, 2018)
This paper shows how an American International School in Vietnam has been using data and Learning Analytics to find out about students’ learning from their assessments and how they use these findings to improve, among other areas, the reading skills of their mostly English as an Additional Language (EAL) student population. The source of data comes primarily from a Computer Adaptive Testing platform, commonly known as the MAP Growth test, which provides information about Math and Reading skills for each particular student.The data provided is transformed and presented to educational stakeholders through visualizations created in specialized software in order to dig into the data and answer the pedagogical questions emerged from teachers and administrators. This process involves a new field known as Learning Analytics and Visual Data Mining in order to find new information not usually evident in school datasets. The results indicate that teachers get immersed in a reflective process that improves student learning through action plans informed by learning analytics (LA); which could be seen as the scientific data behind the observations educators have traditionally done.
Keywords: Data; Reading; Student Learning; Learning Analytics